Activation of phosphatidylcholine signalling during oxidative stress in synaptic endings - Mateos, Melina Valeria (2008)
The purpose of the present study was to investigate the involvement of phosphatidylcholine (PC) signalling in synaptic endings incubated under oxidative stress conditions. Synaptosomes purified from adult rats (4 months old) cerebral cortex were exposed to oxidative insult (FeSO4, 50 μM) or vehicle, and diacylglycerol (DAG) generation and free fatty acid (FFA) release were subsequently evaluated using exogenous [14C]PC as substrate. DAG formation increased after 5, 30, and 60 min of Fe2+-exposure with respect to the control conditions. The contribution of PC-specific phospholipase C (PC-PLC) and phospholipase D (PLD) pathways to DAG generation was evaluated using ethanol in the enzyme assays. Phosphatidylethanol (PEth) production was measured as a marker of PLD activity. In the presence of ethanol (2%) iron significantly stimulated DAG and PEth production at all times assayed. FFA release from PC, however, was inhibited after 5 and 60 min of iron exposure. Similar results were observed in aged animals (28 months old) when compared with adult animals. DAG generation from PC was also evaluated in the presence of the tyrosine kinase inhibitors genistein and herbimycin A. Inhibition of tyrosine kinase activity did not modify the stimulatory effect exerted by iron on PC-PLC and PLD activities. Moreover, the presence of LY294002 (a specific PI3K inhibitor) did not alter DAG production. Our results demonstrate that oxidative stress induced by free iron stimulates the generation of the lipid messenger DAG from PC in synaptic endings in adult and aged rats.